2016
DOI: 10.18632/oncotarget.10244
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling geneARID2targets cyclin D1 and cyclin E1 to suppress hepatoma cell progression

Abstract: Exome and whole-genome sequencing studies have drawn attention to the role of somatic mutations in SWI/SNF chromatin remodeling complexes in the carcinogenesis of hepatocellular carcinoma (HCC). Here, we explored the molecular mechanisms underlying the biological roles of AT-rich interactive domain 2 (ARID2) in the pathogenesis of HCC. We found that ARID2 expression was significantly downregulated in HCC tissues compared with non-tumorous tissues. Restoration of ARID2 expression in hepatoma cells was sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Previously, we and others reported that ARID2 deficiency is prevalent in human HCC, suggesting that ARID2 deletion may play an important role in the pathogenesis of HCC. (15,20) However, the relationship between HBV infection and ARID2 expression in hepatoma cell lines is unclear. We first examined the levels of ARID2 in an HBV-expressing hepatoma cell line.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we and others reported that ARID2 deficiency is prevalent in human HCC, suggesting that ARID2 deletion may play an important role in the pathogenesis of HCC. (15,20) However, the relationship between HBV infection and ARID2 expression in hepatoma cell lines is unclear. We first examined the levels of ARID2 in an HBV-expressing hepatoma cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Following elution, DNA was extracted and subjected to PCR analysis. Isolated chromatin immunoprecipitated by E2F1 antibody was amplified with ARID2 primers and CCND1 (cyclin D1) primers used us positive control . For ChIP‐qPCR, the immunoprecipitated DNA was quantified by real‐time PCR.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations